Student-teachers’ technological pedagogical content knowledge preparedness for mathematics instruction - Anita Larteley Addico; Clement Ayarebilla Ali; Nixon Saba Adzifome (Journal of Advanced Sciences and Mathematics Education, 2022)
The study aimed to assess student-teachers preparedness for technological pedagogical content knowledge of Mathematics instruction. The design was the survey, and the sampling technique was the simple random technique. A structured questionnaire was used to collect data to analyze the research questions. The data for research question one was analyzed using means and standard deviations, while we used a One-way Multivariate Analysis of Variance to analyze data for research question two. The results and findings revealed that student-teachers were generally prepared. However, they were more prepared for technological knowledge. This was depicted in the significant differences in preparedness. It was concluded that stakeholders assess the content needs and include mathematical models that address needs, pedagogy, and content knowledge. This finding calls for continuous updates of the mathematics curriculum to ensure comprehensive and effective preparedness.